2021
DOI: 10.3390/su13147953
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Spatiotemporal Evolution of the Green Dam in Djelfa Province, Algeria

Abstract: Green walls and green dams are increasingly being considered as part of many national and international desertification initiatives. This paper studies the spatiotemporal evolution of the green dam in the Moudjbara region (Djelfa Province, Algeria), from 1972 to 2019, by using Landsat imagery, Land Change Modeler, and OpenLand package. The future evolution of pine plantations, for the year 2029, was also forecasted, based on an anthropogenic scenario (i.e., anthropogenic pressure is the main driver of the gree… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…However, the survival rate was very poor until the 21st century due to a prolonged drought in the 1980s, without achieving the expected performance (Belala et al., 2018). It is worth noting that in Algeria, human activities rather than climate have mainly affected the vegetation coverage since the 21st century, with an exponential increase in the livestock numbers in the green dam areas, which increased the wind erosion risk (Benhizia et al., 2021). The results of Section 3.3 of this study showed that the wind erosion change was determined by wind speed in the GD area over the past 20 years, while changes in vegetation coverage had a minor effect on wind erosion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival rate was very poor until the 21st century due to a prolonged drought in the 1980s, without achieving the expected performance (Belala et al., 2018). It is worth noting that in Algeria, human activities rather than climate have mainly affected the vegetation coverage since the 21st century, with an exponential increase in the livestock numbers in the green dam areas, which increased the wind erosion risk (Benhizia et al., 2021). The results of Section 3.3 of this study showed that the wind erosion change was determined by wind speed in the GD area over the past 20 years, while changes in vegetation coverage had a minor effect on wind erosion.…”
Section: Discussionmentioning
confidence: 99%